Heraldic Hierarchies : Identity, Status and State Intervention in Early Modern Heraldry - Duerloo, L.; Thiry, Steven (Leuven University Press, 2021)
Early modern heraldry was far from a nostalgic remnant from a feudal past. From the Reformation to the French Revolution, aspiring men seized on these signs to position themselves in a changing society, imbuing heraldic tradition with fresh meaning. Whereas post-medieval developments are all too often described in terms of decadence and stifling formality, recent studies rightly stress the dynamic capacity of bearing arms. 'Heraldic Hierarchies' aims to correct former misconceptions. Contributing authors rethink the influence of shifting notions of nobility on armorial display and expand this topic to heraldry's share in shaping and contesting status. Moreover, addressing a common thread, the volume explores how emerging states turned the heraldic experience into an instrument of power and policy. Contributing to debates on social and noble identity, 'Heraldic Hierarchies' uncovers a vital and surprising aspect of the pre-modern hierarchical world.